2008
DOI: 10.1111/j.1479-828x.2008.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of the Perigee system for the management of cystocoeles – Medium‐term follow up

Abstract: On medium-term evaluation (18 to 36 months) of the Perigee system the results seem very encouraging. The morbidity is minimal, as is the recurrence and mesh extrusion rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 16 publications
2
16
1
2
Order By: Relevance
“…The TVM types include Perigee® (AMS Inc., Minnetonka, MN, USA), Avaulta A (Avaulta Anterior Plus BioSynthetic Support System, C. R. Bard, Inc., Murray Hill, NJ, USA), Prolift T (Gynecare PROLIFT Anterior and Posterior Pelvic Floor Repair Systems, Ethicon, Inc., Somerville, NJ, USA), and Elevate A (Elevate® Anterior and Apical Prolapse Repair System, AMS Inc., Minnetonka, MN, USA). Details of the surgical procedures were as described previously for Perigee [15,16], Avaulta A [17], Prolift T [18], and Elevate A [19]. SSF was performed by adopting the right unilateral posterior approach as described by Miyazaki [20].…”
Section: Operative Proceduresmentioning
confidence: 99%
“…The TVM types include Perigee® (AMS Inc., Minnetonka, MN, USA), Avaulta A (Avaulta Anterior Plus BioSynthetic Support System, C. R. Bard, Inc., Murray Hill, NJ, USA), Prolift T (Gynecare PROLIFT Anterior and Posterior Pelvic Floor Repair Systems, Ethicon, Inc., Somerville, NJ, USA), and Elevate A (Elevate® Anterior and Apical Prolapse Repair System, AMS Inc., Minnetonka, MN, USA). Details of the surgical procedures were as described previously for Perigee [15,16], Avaulta A [17], Prolift T [18], and Elevate A [19]. SSF was performed by adopting the right unilateral posterior approach as described by Miyazaki [20].…”
Section: Operative Proceduresmentioning
confidence: 99%
“…The high anatomical cure rate of synthetic mesh use in cystocele surgery in our series is comparable to that in the literature. 30 Most of the studies are prospective follow-up studies, [31][32][33][34] with only a limited number of randomised controlled trials comparing the use of anterior polypropylene mesh with anterior colporrhaphy. [22][23][24]27 These randomised controlled trials differ from our study with respect to the use of interpositioning of the mesh instead of our transobturator fixation, 23,24,27 the use of a mixed population of women with both primary and repeated cystocele repair instead of only primary cases, 22,27 the use of non-validated symptom and quality of life questionnaires, 27 and the use of a mixed population of cystocele and rectocele repairs.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Paraiso was the only one to report a pelvic abscess after surgery [5]. In 11 non-randomized studies (623 patients), nine of which using NAS meshes, no post-surgical infection was detected [33,[36][37][38][39][40][41][42][43][44][45]. Six studies with NAS meshes reported post-surgical hyperthermia, meaning 3.15% out of 755 cases [46][47][48][49][50][51].…”
Section: Infectionmentioning
confidence: 99%